SME innovation and learning: the role of networks and crisis events. Issue 1 (6th January 2014) - Saunders, Mark N.K.; Gray, David E; Goregaokar, Harshita
Abstract : Purpose: – The purpose of this paper is to contribute to the literature on innovation and entrepreneurial learning by exploring how SMEs learn and innovate, how they use both formal and informal learning and in particular the role of networks and crisis events within their learning experience. Design/methodology/approach: – Mixed method study, comprising 13 focus groups, over 1, 000 questionnaire responses from SME managers, and 20 case studies derived from semi-structured interviews. Findings: – SMEs have a strong commitment to learning, and a shared vision. Much of this learning is informal through network events, mentoring or coaching. SMEs that are innovative are significantly more committed to learning than those which are less innovative, seeing employee learning as an investment. Innovative SMEs are more likely to have a shared vision, be open-minded and to learn from crises, being able to reflect on their experiences. Research limitations/implications: – There is a need for further process driven qualitative research to understand the interrelationship between, particularly informal, learning, crisis events and SME innovation. Practical implications: – SME owners need opportunities and time for reflection as a means of stimulating personal learning – particularly the opportunity to learn from crisis events. Access to mentors (often outside the business) can be important here, as are informal networks. Originality/value: – This is one of the first mixed method large scale studies to explore the relationship between SME innovation and learning, highlighting the importance of informal learning to innovation and the need for SME leaders to foster this learning as part of a shared organisational vision.